Geopolitics and Language in the Christopher Columbus Era - Koch–Kozhuharova, Daniela (Research Papers, 2020)
The research is aiming to approach Geopolitics in the Columbus era by diachronic comparative analysis based on the eternal axis values-interests. The broad range ofmultifaceted opinions with regard to the assessment of America’s conquest by the so calledconquistadors was launched by the Spaniards themselves, who were contemporaries of the historic events that took place back then, events which, to quote Tsvetan Todorov, made the world a closed place by their attempts to frame in both legislative and moral terms the emerging social, economic and other relations „with” and ”on” the newly discovered territories. In the more modern times, these assessments in Spain acquire political dimensions, facilitating in scope between descriptions such asphysical and cultural genocide to knightly courage in the name of Christ. However, there is no doubt that what serves as grist in the mill, whether justifiably or not, in the vilification of the Spanish enterprise are the political rivals of Spain back in the 15th century, when the country did not shy away from transforming itself within less than a year from a territory that had been dominated for centuries on end by the Arabs to an expansionistic country. While the Anglo-Saxon model for invasion creates preserves, the Spanish model creates a society of  mestizos, mulattos and creols. Thе pathos of denial is now-a-days partially calmed down and an entire continent speaks Spanish, while the globalizing world is dancing to thelatino rhythm.
Keywords: Geopolitical orientation; Expansion; Language; Values; Foreign policy